2015
DOI: 10.1007/s11590-015-0982-4
|View full text |Cite
|
Sign up to set email alerts
|

Weak infeasibility in second order cone programming

Abstract: The objective of this work is to study weak infeasibility in second order cone programming. For this purpose, we consider a sequence of feasibility problems which mostly preserve the feasibility status of the original problem. This is used to show that for a given weakly infeasible problem at most m directions are needed to get arbitrarily close to the cone, where m is the number of Lorentz cones. We also tackle a closely related question and show that given a bounded optimization problem satisfying Slater's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…We also developed an analogous bound for second order cone programs. If K is a product of m Lorentz cones, then we have the bound m for the dimension of the affine space [11]. We note that this is tighter than the bound predicted by [8].…”
Section: Recent Developments and Conclusionmentioning
confidence: 70%
“…We also developed an analogous bound for second order cone programs. If K is a product of m Lorentz cones, then we have the bound m for the dimension of the affine space [11]. We note that this is tighter than the bound predicted by [8].…”
Section: Recent Developments and Conclusionmentioning
confidence: 70%
“…We will use the following pair of results to certify infeasibility of (1) in cases where it is primal and/or dual strongly infeasible; we refer the reader to [LMT16] for more details on strong and weak infeasibility.…”
Section: Infeasibility Certificatesmentioning
confidence: 99%
“…From ( 22), ( 23), (24) and recalling that θ ≤ 0, we obtain u, z = 0. This implies that C ⊆ H and θ = 0.…”
Section: Proof: Letmentioning
confidence: 97%
“…In [50], Waki showed that weakly infeasible problems sometimes arise from polynomial optimization. There is also a discussion on weak infeasibility semidefinite programming and second-order cone programming in [22,24], respectively. Some of the results in [22] were generalized to arbitrary closed convex cones by Liu and Pataki, see [18] for more details.…”
Section: Background and Previous Workmentioning
confidence: 99%
See 1 more Smart Citation